2022
DOI: 10.1029/2021gc010123
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Pleistocene to Recent Crustal Extension in the Inner Graben of the Northern Kenya Rift

Abstract: Magmatic continental rifts often constitute nascent plate boundaries, yet long‐term extension rates and transient rate changes associated with these early stages of continental breakup remain difficult to determine. Here, we derive a time‐averaged minimum extension rate for the inner graben of the Northern Kenya Rift (NKR) of the East African Rift System for the last 0.5 m.y. We use the TanDEM‐X science digital elevation model to evaluate fault‐scarp geometries and determine fault throws across the volcano‐tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
1
6
0
Order By: Relevance
“…For regions farther south, in the southern Turkana Rift, Rooney et al (2022) suggested migration of deformation toward a narrow zone accompanied by spatially focused magmatism. Similarly, a recent structural and geochronological study in the nKR documented a significant influence of magmatism associated with Quaternary strain localization within the inner graben of the rift (Riedl et al, 2022), similar to observations made in the central and southern sectors of the Kenya Rift (Baker, 1986;Baker et al, 1988;Strecker et al, 1990).…”
Section: Rifting and Magmatismsupporting
confidence: 77%
See 4 more Smart Citations
“…For regions farther south, in the southern Turkana Rift, Rooney et al (2022) suggested migration of deformation toward a narrow zone accompanied by spatially focused magmatism. Similarly, a recent structural and geochronological study in the nKR documented a significant influence of magmatism associated with Quaternary strain localization within the inner graben of the rift (Riedl et al, 2022), similar to observations made in the central and southern sectors of the Kenya Rift (Baker, 1986;Baker et al, 1988;Strecker et al, 1990).…”
Section: Rifting and Magmatismsupporting
confidence: 77%
“…With respect to the rift‐related magmatic evolution of the study area, it can be concluded that the volcanic rocks in the BRZ were emplaced in three major eruption periods during the Eo‐Oligocene, the Miocene, and the Pliocene‐Holocene. These distinct eruptive episodes were virtually coeval with phases of tectonic activity in the Red Sea Rift (e.g., Bosworth & Stockli, 2016), the eastern Tanzanian Craton (e.g., Rooney, 2020), and the nKR (Muirhead et al., 2022; Riedl et al., 2022).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations